Peningkatan Kompetensi Digital Guru Madrasah Melalui Pelatihan Aplikasi Perkantoran Berbasis Microsoft Office - Ade Irma Purnama Sari; Ade Rizki Rinaldi; Ahmad Syaeful Ma’arief; Alfi Rizqi Falih (CV. Multi Kreasi Media, 2022)
This community service program aims to enhance the digital competence of teachers at Madrasah Tsanawiyah (MTs) in Cirebon City through office application training. Preliminary surveys revealed that the majority of educators lacked optimal skills in using office software such as Microsoft Word, Excel, PowerPoint, and Google Workspace, which negatively impacted administrative efficiency and the quality of digital-based learning. This issue prompted the implementation of an intensive training program using a learning by doing approach, featuring hands-on practice, case studies, and simulations based on real educational needs. The training was conducted in several structured modules, covering basic application use, academic data management, and the development of digital teaching materials. Participants completed assignments and were evaluated through pre-tests and post-tests. Results showed a significant improvement in digital skills, with 80% of participants demonstrating technical progress and 92% expressing satisfaction and finding the training highly beneficial. Furthermore, several madrasahs began adopting digital-based administrative systems, indicating a tangible impact on digital transformation within educational institutions. Program outcomes include digital training modules, ready-to-use administrative document templates, and improved teacher capacity in data management and the development of engaging learning content. This initiative also fostered greater awareness of the importance of digital literacy among educators and opened up opportunities for sustained professional development through follow-up mentoring and advanced training sessions. Overall, the program successfully contributed to improving educational quality and teacher efficiency in the digital era.